Chapter Il Brasile nel XVIII secolo - Graziani, Michela (Studi e saggi, 2023)
The third and last section of the volume aims to represent the Brazilian colony in the 18th century through an historical, iconographical and literary point of view, and analyzing three very important Brazilian volumes of the same period.